Potential Nutritive Value and Condensed Tannin Contents of Acorns from Different Oak Species - KAYA, E.; KAMALAK, A. (Kafkas Universitesi Veteriner Fakultesi Dergisi, 2012)
The potential nutritive values of acorns of Quercus suber, Quercus branti, Quercus coccifera, Quercus cerris and Quercus infectoria were estimated by chemical composition and in vitro gas production technique. Acorns collected at least 10 different trees in three experimental plots. There were significant (P<0.001) differences in the chemical composition among acorns obtained from different oak species. Crude protein (CP) contents of acorns ranged from 25.48 to 61.94 g/kg dry matter (DM). Neutral detergent fiber (NDF) contents ranged from 231.4 to 326.3 g/kg DM. Acid detergent fiber (ADF) contents ranged from 155.9 to 215.4 g/kg DM. Condensed tannin (CT) contents ranged from 7.2 to 26.7 g/kg DM. Starch contents ranged from 600.0 to 681.5 g/kg DM. Polyethylene glycol (PEG) addition significantly (P<0.001) increased the gas production and some estimated parameters of oak acorns. Although there is no significant (P>0.5) differences in the potential gas production of acorn among oak species when incubated in the absence of PEG, there is significant (P<0.001) differences in the potential gas production of acorn among oak species when incubated in the presence of PEG. Although the estimated organic matter (OMD) and metabolisable (ME) contents of acorn for Q. suber and Q. infectoria were significantly (P<0.001) higher than those for Q. branti, Q. coccifera and Q. cerris when incubated in the absence of PEG, the estimated OMD and ME contents of acorn for Quercus cerris and Q. infectoria were significantly lower than those for Q. suber, Q. branti and Q. coccifera when incubated in the presence of PEG. The improvement in gas production, OMD and ME in the presence of PEG emphasizes the negative effect of tannins on digestibility. As a conclusion, oak acorns have potential nutritive values for ruminant animals such as sheep and goat since acorns have high starch, OMD and ME but low level of CT contents. However these results obtained in the current study should be supported by in vivo feeding experiments.
Keywords: Condensed tannin; digestibility; In vitro gas production; Metabolizable energy; oak acorn; Polyethylene glycol

Growth performances , carcasses parameters and meat fatty acid composition of lamb fed green oak acorns ( Quercus ilex ) based diet - Keddam, Ramdane; Bouderoua, Kaddour; El-affifi, Mohamed; Attou, Ghalem Selselet- (African Journal of Biotechnology, 2010)
The aim of this experiment is to compare the effects of diets containing green oak acorns (GO) and barley (BL) on the growth performances, carcasses parameters and the composition in fatty acids of lambs. Two groups of five lambs each were fed, respectively, during 105 days with diets containing 50% of oaks acorns and 50% of barley. At the end of the test, the animals of the two diets expressed comparable body weights and weight gain. A significant difference (P < 0.05) was observed for the thickness of fat cover which is 3 mm for the BL group against 1.6 mm for GO group even if no significant difference was revealed concerning the output with slaughtering. The intramuscular lipids were significantly higher (P < 0.05) in the group of animals fed with GO diet compared to the BL diet (3.88 vs 2.83 g.100-1 g of muscle). Among the saturated fatty acids (SFA), the stearic acid significantly appeared in higher proportion (P < 0.05) in GO diet (20.8 vs 18.1%) whereas the palmitic acid is prevalent in the group of animals fed with the BL diet (25 vs 30%). For the polyunsaturated fatty acid (PUFA), no significant difference was observed between the two groups. The linoleic acid is prevalent among the PUFA of two groups without significant difference. The linolenic acid is higher in the animal fed BL. The n-6: n-3 ratio is higher in the BL group (8.9 vs 7.3). At the end, the low level of incorporation of PUFA in muscle of the lamb because of biohydrogenation, suggests us supplementing the diet by green grass.
Keywords: barley; fatty acid; lamb; meat; oak acorn

Effect of replacing barley grain with cork oak acorn (Quercus Suber L.) on digestibility, nitrogen balance and growth of goat kids. - Aziza, G B; Hedi, A; Hajer, K; Rabia, M (JOURNAL OF ANIMAL SCIENCE, 2006)
The objective of this study was to evaluate the effect of the replacement of barley grain with cork oak acorn (Quercus suber L.) on performance, nutrients intakes, apparent digestibility coefficient and nitrogen balance with growing goats. Ten Boer kids (26.5±2 kg) were individually housed in metabolism cages and were randomly divided into a control (n = 5) and an experimental (n = 5) group. Kids in both groups received (on the basis of crude matter) 500 g/day per head of chopped oat hay and 600 g of concentrate containing barley grain (control group) or oak acorn (experimental group). Digestibility coefficients of dietary components were reduced as a result of acorn substitution for barley. Nitrogen retention (g/day) was positive for experimental group (6.18) but lower than for control group (8.72). The average consumption of digestible components, expressed in g kg-1 LW 0.75 for the control and experimental groups was, respectively, 51.5 and 41.5 (OM) and 7.9 and 6.0 (CP), resulting in weight gains of 80 and 43 g/day.
Keywords: digestibility; kids; oak acorn

Effect of replacing barley grain with cork oak acorn (Quercus Suber L.) on digestibility, nitrogen balance and growth of goat kids. - Aziza, G. B.; Hedi, A.; Hajer, K.; Rabia, M. (JOURNAL OF ANIMAL SCIENCE, 2006)
The objective of this study was to evaluate the effect of the replacement of barley grain with cork oak acorn (Quercus suber L.) on performance, nutrients intakes, apparent digestibility coefficient and nitrogen balance with growing goats. Ten Boer kids (26.5±2 kg) were individually housed in metabolism cages and were randomly divided into a control (n = 5) and an experimental (n = 5) group. Kids in both groups received (on the basis of crude matter) 500 g/day per head of chopped oat hay and 600 g of concentrate containing barley grain (control group) or oak acorn (experimental group). Digestibility coefficients of dietary components were reduced as a result of acorn substitution for barley. Nitrogen retention (g/day) was positive for experimental group (6.18) but lower than for control group (8.72). The average consumption of digestible components, expressed in g kg-1 LW 0.75 for the control and experimental groups was, respectively, 51.5 and 41.5 (OM) and 7.9 and 6.0 (CP), resulting in weight gains of 80 and 43 g/day.
The following values have no corresponding Zotero field: pub-location: 1111 NORTH DUNLAP AVE, SAVOY, IL 61874 USA publisher: AMER SOC ANIMAL SCIENCE
Keywords: digestibility; kids; oak acorn

Fatty acid composition of abdominal adipose tissue in broilers fed green-oak (Quercus ilex), cork oak acorn (Quercus Suber L.) based diets - Bouderoua, Kaddour; Selselet-Attou, Ghalem (Anim. Res., 2003)
Male broilers, 30 for every diet, were fed for six weeks, diets containing 60% green oak (GO) and oak cork (CO) acorns compared to 60% corn (C). The body weight of the chickens fed the oak acorn-based diets was 25% lower than that of the controls (C). Abdominal adipose tissue (AAT) was twice heavier in the controls compared to broilers fed oak acorn-based diets. The total lipids of AAT were higher in the controls compared to the oak acorn fed chickens (34.4 against 15.3 g per 100 g of AAT in the CO). The palmitic and oleic acid proportions were comparable in the AAT of chickens fed with the different diets. The proportion of linoleic acid, obtained exclusively by the diets, was significantly higher in the chickens fed oak acorn-based diets (23%), compared to the controls (19%). Reciprocally, palmitoleic acid was present in a small proportion in chickens fed oak acorns (4 to 5%). The observed variation of the fatty acid content of abdominal fat of acorn-fed chickens requires further research on the precise nutrient digestibility of oak acorns before considering them as a potential feed.
Keywords: Adipose Tissue; broilers; Lipids; lipogenesis; oak acorn

Fatty acid composition of abdominal adipose tissue in broilers fed green-oak (Quercus ilex), cork oak acorn (Quercus Suber L.) based diets - Bouderoua, Kaddour; Selselet-Attou, Ghalem (Anim. Res., 2003)
Male broilers, 30 for every diet, were fed for six weeks, diets containing 60% green oak (GO) and oak cork (CO) acorns compared to 60% corn (C). The body weight of the chickens fed the oak acorn-based diets was 25% lower than that of the controls (C). Abdominal adipose tissue (AAT) was twice heavier in the controls compared to broilers fed oak acorn-based diets. The total lipids of AAT were higher in the controls compared to the oak acorn fed chickens (34.4 against 15.3 g per 100 g of AAT in the CO). The palmitic and oleic acid proportions were comparable in the AAT of chickens fed with the different diets. The proportion of linoleic acid, obtained exclusively by the diets, was significantly higher in the chickens fed oak acorn-based diets (23%), compared to the controls (19%). Reciprocally, palmitoleic acid was present in a small proportion in chickens fed oak acorns (4 to 5%). The observed variation of the fatty acid content of abdominal fat of acorn-fed chickens requires further research on the precise nutrient digestibility of oak acorns before considering them as a potential feed.
Keywords: Adipose Tissue; broilers; Lipids; lipogenesis; oak acorn